Evolution of vocal diversity through morphological adaptation without vocal learning or complex neural control - García, Sarah M. (2017)
The evolution of complex behavior is driven by the interplay of morphological specializations and neuromuscular control mechanisms [1-3], and it is often difficult to tease apart the respective contributions of these two factors. Avian vocal learning and its associated neural adaptations are thought to have played a major role in the diversification of birds [4-8], whereas the functional significance of the substantial morphological diversity of the vocal organ itself remains largely unexplored. Within the most species rich order, Passeriformes, ?tracheophones? are a suboscine group that, unlike their oscine sister taxon, does not exhibit vocal learning [9] and are thought to phonate with a pair of tracheal membranes [10, 11] instead of the two independent sources found in other passerines [12-14]. Here we provide direct videoscopic evidence that tracheophones possess three sound sources, two oscine-like labial pairs in addition to the unique tracheal membranes, which collectively represent the largest described number of sound sources for a vocal organ. Birds with experimentally disabled tracheal membranes were still able to phonate. Instead of being the main sound source, the tracheal membranes constitute a morphological specialization, which, through interaction with the labia, contributes to the generation of different acoustic features such as spectral complexity, amplitude modulation and enhanced sound amplitude. In contrast, these same features arise in oscines from neuromuscular control of the two labial sources [15-17]. These findings are supported by a modeling approach and provide a clear example for how a morphological adaptation of the tracheophone vocal organ can generate specific, complex sound features. Morphological specialization therefore constitutes an alternative path in the evolution of acoustic diversity to that of oscine vocal learning and complex neural control.